Penyelesaian Wanprestasi dalam Perjanjian Pembiayaan Syariah - Salsabila Firdaus; Rizalatul Maghfiroh (Cashless : Journal of Sharia Finance and Banking, 2025)
This article aims to analyze the mechanisms for resolving defaults in Islamic financing agreements within Islamic financial institutions, highlighting the alignment of these practices with Sharia principles, particularly justice and the avoidance of usury, and identifying challenges and solutions to enhance their effectiveness. A thorough theoretical review of the concept of default in Islamic law, the principles of Islamic finance, and resolution mechanisms forms the basis of the analysis. The findings of the discussion indicate that Islamic financial institutions generally prioritize deliberation, restructuring, and mediation before resorting to arbitration or litigation. Ensuring the alignment of practices with Sharia principles requires strict oversight and consistent interpretation. Challenges such as differing understandings of Sharia principles and customer financial literacy can be addressed through regulatory standardization, education, strengthening the Sharia Supervisory Board, and leveraging technology. This article concludes that the resolution of defaults in Islamic financing should be based on justice and deliberation, with sanctions aimed at maintaining a balance of rights and obligations without involving usury, for the sustainability of a sound and equitable Islamic financial industry.